Regioselective Metal‐ and Reagent‐Free Arylation of Benzothiophenes by Dehydrogenative Electrosynthesis. Issue 40 (28th August 2018) - Lips, Sebastian; Schollmeyer, Dieter; Franke, Robert; Waldvogel, Siegfried R.
Abstract: A novel strategy for the synthesis of biaryls consisting of a benzothiophene and a phenol moiety is reported. These heterobiaryls are of utmost interest for pharmaceutical, biological, and high‐performance optoelectronic applications. The metal‐ and reagent‐free, electrosynthetic, and highly efficient method enables the generation of 2‐ and 3‐(hydroxyphenyl)benzo[ b ]thiophenes in a regioselective fashion. The described one‐step synthesis is easy to conduct, scalable, and inherently safe. The products are afforded in high yields of up to 88 % and with exquisite selectivity. The reaction also features a broad scope and tolerates a large variety of functional groups. Abstract : High selectivity for position 2 or 3 of the benzothiophene is a key feature of anodic C−C cross‐couplings with phenols reacting at the ortho or para position. The electrochemical process exploits the HFIP‐directed dehydrogenative cross‐coupling in a reagent‐ and metal‐free manner and is inherently safe and scalable.